A case of 14q11.2 microdeletion with autistic features, severe obesity and facial dysmorphisms suggestive of Wolf–Hirschhorn syndrome. Issue 1 (15th November 2013) - Terrone, Gaetano; Cappuccio, Gerarda; Genesio, Rita; Esposito, Annalisa; Fiorentino, Valeria; Riccitelli, Marina; Nitsch, Lucio; Brunetti‐Pierri, Nicola; Del Giudice, Ennio
ABSTRACT We report on a 21‐year old woman with intellectual disability, autistic features, severe obesity, and facial dysmorphisms suggestive of Wolf–Hirschhorn syndrome (WHS). Array‐CGH analysis showed a 2.89 Mb deletion on chromosome 14q11.2 containing 47 known genes. The most interesting genes included in this deletion are CHD8, a chromodomain helicase DNA binding protein that is associated with autism spectrum disorders, and MMP14, a matrix metalloproteinase that has been linked to obesity and type 2 diabetes. This report shows that 14q11.2 microdeletions can mimic WHS and suggests that gene(s) in the deleted interval that may be responsible for a phenocopy of WHS. © 2013 Wiley Periodicals, Inc.